Early season pediatric influenza B/Victoria virus infections associated with a recently emerged virus subclade — Louisiana, 2019. Issue 2 (26th January 2020) - Owusu, Daniel; Hand, Julie; Tenforde, Mark W.; Feldstein, Leora R.; DaSilva, Juliana; Barnes, John; Lee, Grace; Tran, Juliet; Sokol, Theresa; Fry, Alicia M.; Brammer, Lynnette; Rolfes, Melissa A.
Abstract : This report summarizes early influenza activity, demonstrating an unusual preponderance of influenza B early in this year's season.